Effect of Al3Ni and SiC on Mechanical and Wear Behaviour of Al-Ni-SiC Composite - Mahali M.; Sinha N.K.; Choudhary I.N.; Singh J.K.; Mohan S. (My University, 2025)
The present article discusses the combined effect of SiC reinforcement particle and in-situ formed Al3Ni on the mechanical and wear behavior of Al-Ni-SiC composite. The composite was subjected to examination through microstructure, mechanical and wear properties. The dry sliding pin-on-disc tribometer was utilized to study the wear behaviour of composite at a varying load of 10–20 N and velocities of 1—1.5 m/s with 1500 m sliding distance. Microstructure reveals the formation of in-situ Al3Ni phase and homogeneous distribution of SiC throughout the matrix. At the same time, it was also indicated that the presence of Al3Ni phase i.e., hard particle and SiC reinforcement improved the mechanical and wear properties of Al-Ni-SiC composite. The compressive strength and hardness of the composite increase consistently as the reinforcement particle increases. The composite having 16 wt.% SiC shows the high compressive strength and hardness of 732.48 MPa, 49 HV respectively. Composite having 4 wt.% SiC at high load 20 N with each frequency indicates the high wear rate of the given composite. The result of worn surface analysis may be predicted the nature of wear mechanism either adhesive or abrasive with oxidative in nature. The X-Ray Diffraction (XRD) of wear debris also confirms the oxidative nature of wear mechanism. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.